8B.06: BAROREFLEX ACTIVATION THERAPY CONSISTENTLY MAINTAINS BLOOD PRESSURE REDUCTION IN A LARGE RESISTANT HYPERTENSION COHORT FOR AT LEAST 6 YEARS. (June 2015) - de Leeuw, P. W.; Bakris, G.L.; Nadim, M.K.; Haller, H.; Lovett, E.G.; Bisognano, J.D.
Abstract : Objective: Previous reports have indicated that blood pressure (BP) reductions imparted by baroreflex activation therapy (BAT) in patients with resistant hypertension (rHTN) are maintained for at least 5 years. Because such reports have focused only on patients who remain active, it is possible that selection bias could overstate the impact of BAT. The purpose of this investigation is to comprehensively describe long-term BP reductions in rHTN patients receiving BAT using all data currently available. Design and method: Following collection of the pre-specified 12-month endpoints, patients were followed every 6 months. BP data were collected at each follow-up using a protocol-defined technique to minimize bias. Results: Original trial enrollment consisted of 322 patients. Of those, 182 presently remain active while 140 are inactive due to withdrawal from the study (112) or death (28). Consistent with earlier reports, BP reductions were > 30/15 mmHg for at least 6 years. Long-term therapy safety was excellent with low rates of stroke, myocardial infarction and hypertensive urgency. Figure. No caption available. Conclusions: BAT-induced BP reductions in rHTN patients were remarkably consistent over time, maintaining high levels of clinical and statistical significance. Previous reports of only active patients faithfully represent the true course of BP response to BAT in a large rHTN cohort.